To solve the system of equations using substitution, we start with the two equations:
- \( y = 2 + 3x \)
- \( 4x - 3y = -16 \)
We can substitute the expression for \( y \) from the first equation into the second equation.
Substituting \( y \) in the second equation: \[ 4x - 3(2 + 3x) = -16 \]
Now, simplify: \[ 4x - 6 - 9x = -16 \]
Combine like terms: \[ -5x - 6 = -16 \]
Add 6 to both sides: \[ -5x = -10 \]
Now, divide by -5: \[ x = 2 \]
Now that we have \( x \), we can substitute it back into the first equation to find \( y \): \[ y = 2 + 3(2) = 2 + 6 = 8 \]
So, the solution to the system of equations is: \[ (x, y) = (2, 8) \]
The correct answer is \( \boxed{(2, 8)} \).